Delayed motherhood and its determinants among women of reproductive age in five Sub-Saharan African Countries: A multilevel analysis of recent demographic and health surveys (2021–2023) - Yilkal Abebaw Wassie; Tekletsadik Tekleslassie Alemayehu; Tsehayu Melak Siyoum; Girum Nakie; Getasew Kibralew; Gebresilassie Tadesse; Zemenu Wube Bayleyegn; Berihun Agegn Mengistie; Gashaw Sisay Chanie; Tesfaye Birhanu Abebe; Leul Dejene Abate; Cherugeta Kebede Asfaw; et al. (PLoS ONE, 2025)
Introduction In recent years, more women have delayed childbearing until their late twenties or early thirties, a time when reproductive potential declines, thereby making conception more challenging with advancing age. While delayed motherhood is widely reported, there is limited research on its underlying causes in Sub-Saharan Africa. Exploring these factors offers valuable insights for researchers, policymakers, and healthcare providers. Method This study used the most recent Demographic and Health Surveys (2021–2023) across five Sub-Saharan Africa countries. A weighted sample of 47,439 women of reproductive age were analyzed using Stata 14. The determinants of delayed motherhood were determined using a multilevel mixed-effects logistic regression model. Statistical significance was determined at p-values <0.05, and results were reported using adjusted odds ratio (AOR) with 95% confidence interval. Results A total of 47,439 study participants were enrolled in the study. The mean age was 31.9 years (±8.7 SD), with over half (54.54%) aged between 20 and 35 years. The prevalence of delayed motherhood among women of reproductive age in Sub-Saharan Africa was 61.94%. Individual factors such as did not have occupation (AOR = 1.65, 95% CI: 1.57, 1.73), whose husband did not have occupation (AOR = 1.55, 95% CI: 1.51, 1.78), and those with poor wealth status (AOR = 2.62, 95% CI: 1.58, 3.66) were more likely to delay motherhood. Moreover distance to a health facilities (AOR = 1.04, 95% CI: 1.09, 1.39), urban residence (AOR = 2.48, 95% CI: 1.67, 2.09), and high community illiteracy (AOR = 3.24, 95% CI: 1.55, 5.35) were also significant predictors of delayed motherhood. Conclusions This study reveals a significant prevalence of delayed motherhood among women of reproductive age in Sub-Saharan Africa. Major contributing factors include unemployment, poverty, urban residence, limited healthcare access, and community illiteracy. Addressing these disparities requires targeted policies and improved access to education and healthcare services.